Reducing spending and increasing equity: how far can refundable tax credits take us? - Hum, Derek; Simpson, Wayne (1995)
The social security review now underway is intended to restructure Canada's social safety net. The principle of universality is likely to be replaced by income-conditioned transfers with improved work incentives. At the same time, the notion of a refundable tax credit lurks in the background, a legacy of the first social security review held in the 1970s. Our paper examines the rationale behind the income-testing principle, the structure of refundable tax credit plans and their relationship to income inequality in Canada. More specifically, a number of differently configured refundable tax credit options are simulated using Canadian household micro-data to evaluate the budgetary costs, the implied average tax rate required to finance the program and the resulting degree of inequality. We demonstrate the possibility of cutting government spending while simultaneously reducing income inequality in Canada. - Reproduced
Keywords: Inequality - Canada; Income distribution - Canada; Taxation - Canada; Taxation